Evaluation of water quality parameters, growth and proximate composition of juvenile crab, Portunus pelagicus cultured in RAS and non RAS system - S.M. Shoyaib Kohinoor,; Aziz Arshad,; S.M. Nurul Amin,; Mohd Salleh Kamarudin,; Muhammad Aliyu Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Juvenile blue swimming crab, Portunus pelagicus were reared over 31 days in two different systems namely recirculating aquaculture system (RAS) and conventional aquaculture system (CAS) to evaluate the water quality parameters, growth, and its body composition. The juvenile crab, weighing of 0.95 ± 0.18 g and stocking was at 40 crabs m-2 and fed twice per day with a commercial shrimp pellet. During the experimental time, significantly (P <0.05) increment in dissolved oxygen (DO) (6.42 ± 0.13), low level of ammonia- nitrogen (0.04 ± 0.10) and nitrite-nitrogen (0.04 ± 0.10) were recorded in RAS than conventional aquaculture system (CAS) (DO: 5.99 ± 0.24; ammonia- nitrogen: 3.83 ± 1.59; nitrite-nitrogen: 0.71 ± 0.58). The carapace width, weight gain and specific growth rate (SGR) were significantly (P <0.05) higher in RAS. Protein content (22.65 ± 0.11%) in crab also were significantly (P <0.05) higher in RAS compared with crab protein (21.41 ± 0.12%) cultured in CAS. Although the survival rate was slightly higher in the juveniles reared at CAS, however it was not significantly different comparing with the individuals reared at RAS. The results strongly suggested that the use of RAS may improve the growth performance and maintain the better water quality for the crabs in captivity.